ADMINISTRATION COUNCIL’S IMPACT ON THE PUBLIC ENTERPRISE: THE CASE OF MOROCCO - EL IDRISSI AZIZ; EL YOUSFI HICHAM (Revue Marocaine de Recherche en Management et Marketing, 2020)
The public (or state) enterprise manages a large part of thecollective heritage in most countries, so it is incumbent on it to comply with strict and rigorous governance criteria. In Morocco, the governance of public enterprises occupies more and more an important place in the main strategic orientations of the government. This importance is also present in Moroccan public opinion, especially with the various events that have marked the MENA region (the Arab Spring for example).However, given this interest in the public enterprise, the inventory of the empirical literature does not provide a clear picture of the impact of governance on this structure.On the other hand, examining the theoretical field into which the developments that deal more or less directly with the governance of companies, and more particularlythe public company, gives rise to a double feeling: On the one hand, with regard to our research objective, we remain dissatisfied with the explanations provided by a good number of analyses which hardly provide answers to questions about the specificity of the public enterprise in general, and in terms of governance, in particular.On the other hand, we are struck by the diversity of approaches that attempt to partially answer these questions without providing a comprehensive and multidimensional approach.In addition, most of the analyses encountered ignore aspects of public enterprises operating in developing countries. Empirically, however, the results of the many studies carried out so far are, on the whole, ambiguous and therefore do not support the unequivocal conclusion that there is a relationship between the form of ownership and performance.In addition, the governance of a company, whether private or public, involves several mechanisms (social networks, mutual control of managers, control by shareholders, etc.), nevertheless the administration’s council remains the most evoked tool, since it constitutes a means of direct control of shareholders.However, given the ambiguity presented by the impact of the administration’s council on the performance, of the public company in particular, with all the points of difference or resemblance that it presents compared to a private firm, from this research, we will aim to propose a new research model. The objective is to obtain more relevant answers concerning the effects of the administration’s council on the creation of values. To this end, we will build, on the basis of the synthetic theory of corporate governance, a modelcombining the arguments of disciplinary and cognitive approaches . To obtain satisfactory answers concerning the impact of the administration’s council on the creation of values of the public enterprise, we will operationalize the performance both by a measure of the return on assets as by a criterion of return on equity. To examine the validity of the many research hypotheses, we will begin regression analyzes in the form of panel data. The advantage of this method consists of the fact that it allows to take into account the transverse dimensions (instantaneous cuts) and longitudinal (temporal dimension). The analysis ends with a synthesis of the main results and their interpretation.This research work therefore aims to apply the synthetic approach of the government of the public enterprise in the Moroccan case in order to provide more satisfactory answers to the following question: "What are the impacts of a governance mechanism such as the administration council on the performance of the public company? "